Analysis of The Impact of The Russia-Ukraine War on Finland's Policy Using the Neorealism Perspective - Amalia, Novi Rizka; El Zahidin, ‘Azzam; Ardiyanti, Dwi (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
The Russia-Ukraine war has changed Northern European security, threatening Finland's national security. War has a systemic impact not only on the conflicting nations but also on the security of other nations. Thus, Finland must strengthen its national security defense capabilities, including shifting its 74-year-old neutrality policy into alliance policy and joining NATO. One reason NATO is important is that Article 5 guarantees Finland's security. Article 5 briefly states that an external attack on one alliance member state affects all members. Finland's alliance with NATO, which has 3.3 million troops and various defense technologies and deterrence programs, including nuclear deterrence, helps prevent Russian attacks on Finnish national security and balances power with Russia. And to prevent Russia from becoming a hegemon and Finland from being attacked due to unbalanced cost-benefit considerations. The objective of this study is to analyze how the Russia-Ukraine war impacted Finnish national security policy using a neorealism perspective. This research used a qualitative method, focusing on scientific articles from journals and books related to the research title. Qualitative research describes phenomena accurately using words based on relevant data analysis collection techniques and scientific situations to reveal social situations. According to neorealism, Finland's actions were meant to achieve national security in an anarchic international structure. One effort is the NATO alliance policy. The Russia-Ukraine war changed Finland's neutrality policy. Finland's military integration with NATO allowed it to balance power with Russia and deter Russian attacks.